Glial fibrillary acidic protein autoimmunity in reversible splenial lesion syndrome: diagnostic and therapeutic implications - Lin, Lingling; Li, Xiang; Quan, Chao; Zhangbao, Jingzi; Tan, Hongmei; Wang, Yi; Xu, Siyuan; Dai, Zhihao (Frontiers in Neurology, 2025)
Autoimmune GFAP astrocytopathy (GFAP-A) is a neuroinflammatory condition that often involves the brain, meninges, and spinal cord. Its characteristic MRI finding consists of linear or radial perivascular enhancement adjacent to the ventricles. While corpus callosum splenium lesions occur in only 5% of cases, association with reversible splenial lesion syndrome (RESLES) is very rare. In such instances, GFAP-A can clinically resemble viral encephalitis, making diagnosis difficult. This article discusses how to distinguish GFAP-A from viral encephalitis using clinical and auxiliary examinations when RESLES is present.